(untitled) (Open Academia: Journal of Scholarly Research, 2023)
Geological exploration, oil and gas production from the chalk deposits on the southeastern part of the Southern stage of the Fergana intermountain depression are explored and analyzed. Recommendations forincreasing oil and gas production were issued.